THE USE OF TEACHER TALK IN TEACHING ENGLISH LANGUAGE AT SMP N 8 SUNGAI PENUH - Seprita Sari; Ratmanida Ratmanida (English Language Teaching and Research, 2017)
Teaching is commonly defined as a process to transfer knowledge or information to the students. In transfering the knowledge, building communication with students is important for the teachers. The sentences that are used by the teachers can be medium of the students to achieve course objectives in learning English language. This study is conducted to find out the types of teacher talk are used by English teacher in teaching English language at SMP N 8 Sungai Penuh. It was conducted by using descriptive research. The participants in this study were English teachers who teach English and the students who learn English at SMP N 8 Sungai Penuh. The findings reveal that the teachers used referential question, display question, content feedback, Initiation Respond and Feedback sequence, student initiated to talk during teaching and learning English process occured. Key words: English teacher, teacher talk, teaching English language.